Prevalence, Molecular Characterization and Antimicrobial Susceptibility of Clostridioides difficile Isolated from Pig Carcasses and Pork Products in Central Italy - Caterina Licciardi (MDPI AG, 2021)
In the last decade, the incidence and severity of Clostridioides difficile infections (CDIs) in humans have been increasing and community-associated infections have been described. For these reasons, the interest in C. difficile in food and in food animals has increased, suggesting other possible sources of C. difficile acquisition. This study evaluated the presence of C. difficile on pig carcasses at the slaughterhouse and in pork products in Central Italy. The contamination rate on pig carcasses was 4/179 (2.3%). Regarding food samples, a total of 216 pork products were tested (74 raw meat preparations and 142 ready-to-eat food samples made by cured raw meat). The real-time PCR screening was positive for 1/74 raw meat preparation (1.35%) and for 1/142 ready-to-eat food samples (0.7%) C. difficile was isolated only from the raw meat preparation (pork sausage). All the isolated strains were toxigenic and susceptible to all the tested antibiotics. Strains isolated from carcass samples displayed A+B+CDTa+CDTb+ profile, were toxinotype IV and belonged to the same ribotype arbitrary named TV93, while the one isolated from food samples displayed A+B+CDTa-CDTb- profile and it was not possible to determine ribotype and toxinotype, because it was lost after freeze storage. It was concluded that the prevalence of C. difficile in the pork supply chain is very low.